Abdominal Pain in Ulcerative Colitis - Coates, Matthew D. (2013)
BACKGROUND: Chronic pain is common in inflammatory bowel disease (IBD) patients and often attributed to inflammation. However, many IBD patients without evidence of active disease continue to experience pain. This study was undertaken to determine the prevalence of pain in ulcerative colitis (UC) patients and examine the role of inflammation and psychiatric comorbidities in UC patients with pain. METHODS: We performed a retrospective cross-sectional analysis of adult UC patients seen at a tertiary referral IBD center. Age, gender, disease duration and extent, abdominal pain rating, quality of life, physician global assessment (PGA), endoscopic and histologic rating of disease severity, C reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were abstracted. RESULTS: 1268 patients were identified using billing codes for colitis. 502 (48.2% women) met all inclusion criteria. 262 (52.2%) individuals complained of abdominal pain, with 108 (21.5%) individuals describing more frequent pain (‘some of the time or more’). Of those with quiescent disease (n=326), 33 (10%) patients complained of more frequent pain. PGA, endoscopic and histologic severity rating, ESR and CRP significantly correlated with pain ratings. The best predictors of pain were PGA, CRP and ESR, female gender and coexisting mood disorders. CONCLUSIONS: Abdominal pain affects more than 50% of UC patients. While inflammation is important, the skewed gender distribution and correlation with mood disorders highlights parallels with functional bowel disorders and suggest a significant role for central mechanisms. Management strategies should thus go beyond a focus on inflammation and also include interventions that target psychological mechanisms of pain.